Analisis Beban Kerja Mental dan Fisik untuk Upaya Pengendalian Kelelahan di CV. XYZ - Muchtar, Muhammad; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. XYZ is a manufacturing company in East Java that produces various types of concrete, including concrete roof tiles. The contract work system with half-day work hours often causes production targets to be missed, especially for workers who excuse themselves due to illness. This condition has an a impact on increasing the pysical and mental workload using a cardiovascular load (CVL) method and the mental workload using NASA-TLX. The results show that worker 3 at the roof tile printing station 1 had that highest %CVL value, namely 70,53%, and decreased to 59,25% after improvements were made. Meanwhile, worker 4 at the roof tile printing station 2 obtained the highest NASA-TLX score of 80,33, which then decreased to 72,33. This study recommends increasing discipline in the use of PPE and placing workers according to age to improve working conditions.